Kant's copernican Revolution - Bencivenga, Ermanno (Oxford Oxford university press, 1987)
This is a highly original, wide-ranging, and unorthodox discourse on the idea of philosophy contained in Kant's major work, the Critique of Pure Reason. Bencivenga proposes a novel explanation of the Critique's celebrated "obscurity." This great obstacle to reading Kant, Bencivenga argues, has nothing to do with Kant's being a bad writer or with his having anything very complicated to say; rather, it is the natural result of the kind of operation Kant was performing: a universal conceptual revolution. Bencivenga contends that in rejecting the traditional way of doing philosophy, Kant was proposing a paradigm shift comparable in magnitude to Copernicus's overthrow of the Ptolemaic view of the cosmos. Kant, however, was not successful in establishing his idea of philosophy as the new paradigm, and the old view persists in many contemporary versions. Bencivenga argues in favor of Kant's position, which he sees as entailing the view that the role of philosophy is to offer a plausible story about how objectivity might be grounded in certain principles of coherence of our mental states. This book is the story of Kant's revolutionary turnabout, what motivated it, and where it took him; it reveals Kant not only as a figure of historical importance, but as a source of ideas of great contemporary interest.